FRI0022 Anemia is an Independent Predictor of Radiographic Damage Progression in Anti-TNF-Treated Rheumatoid Arthritis Patients from Two Large Phase III Trials. (9th June 2015) - Möller, B.; Florentinus, S.; Ganz, F.; Li, Y.; Kupper, H.; Finckh, A.
Abstract : Background: Progressive joint destruction in rheumatoid arthritis (RA) is associated with inflammation, but damage may progress even in the clinical state of remission. Anemia in patients (pt) with RA is thought to be a result of chronic inflammation, but was recently identified as a marker complementary to disease activity for identification of pts with more rapid erosive disease. 1, 2 Objectives: To study anemia as a predictor of radiographic progression in pts with early and established RA treated with adalimumab (ADA) in controlled studies. Methods: PREMIER was a 2-year (yr) randomized, double-blind (DB), controlled study in methotrexate (MTX)-naïve pts with early RA (mean RA duration 8 months). Pts were randomized to weekly MTX, ADA 40 mg every other week (eow), or MTX + ADA 40 mg eow for 104 weeks (wk). DE019 was a DB, placebo (PBO)-controlled study in established RA (mean RA duration 11 yr) in incomplete MTX responders. Pts were randomized to weekly PBO+MTX, MTX + weekly ADA 20 mg, or MTX + ADA 40 mg eow for 52 wks. A post hoc regression analysis was performed for change from baseline (BL) in modified total Sharp x-ray score (ΔmTSS) to wk 26/24 (PREMIER/DE019), wk 52 (PREMIER and DE019), and wk 104 (PREMIER) using BL anemia status or cumulative wks of anemia as predictor adjusted for pt and disease characteristics, including corticosteroid and NSAID use, and RA disease activity (DAS28). Anemia was defined as lower normal hemoglobin (Hb) limits of 12 g/dL in women and 13 g/dL in men. Central laboratories were used to measure Hb. Results: Anemia was present at BL in 328/799 (41%) pts in PREMIER and 113/619 (18%) pts in DE019. 156/471 (33%) pts in PREMIER and 147/506 (29%) in DE019 without anemia at BL had at least 1 anemia observation during the study. Persistent anemia occurred in 298/799 (37%) pts in PREMIER and 99/619 (16%) in DE019. In PREMIER anemia at BL was associated with ΔmTSS at wk 26 (1.680, P <0.001), wk 52 (2.521, P =0.0011), and wk 104 (4.634, P =0.0003), with the greatest effect at wk 104, compared to no BL anemia. In contrast, in DE019 there was no association between anemia at BL and ΔmTSS at wk 24 or wk 52. However, analysis of presence of anemia over time showed each additional week of anemia resulted in additional ΔmTSS in both studies (PREMIER 0.111 through wk 104, P <0.001, and 0.026 in DE019 through wk 52, P =0.0466). This effect was independent of treatment arm and other covariates. A similar analysis restricted to pts on ADA in PREMIER showed similar cumulative anemia effects on ΔmTSS through wk 104 (0.084, P <0.001). Conclusions: Anemia is a frequent phenomenon even in pts treated with anti-TNFs under controlled trial conditions. The present data confirm anemia as an important predictive parameter for joint damage progression in RA. References: Möller B, et al. Ann Rheum Dis 2014;73:691. van Steenbergen HW, et al. Ann Rheum Dis 2013;72:e16. Acknowledgements: AbbVie funded the studies (NCT00195663, PREMIER; NCT00195702, DE019), contributed to their design and was involved in the collection, analysis, and interpretation of the data, and in the writing, review, and approval of the publication. Medical writing support was provided by Kathleen V. Kastenholz, PharmD, MS, of AbbVie. Disclosure of Interest: B. Möller: None declared, S. Florentinus Shareholder of: AbbVie, Employee of: AbbVie, F. Ganz Shareholder of: AbbVie, Employee of: AbbVie, Y. Li Shareholder of: AbbVie, Employee of: AbbVie, H. Kupper Shareholder of: AbbVie, Employee of: AbbVie, A. Finckh: None declared